À procura de evidências: a transformação da canção sertaneja na obra de Chitãozinho & Xororó sob o enfoque da análise crítica do discurso e da semiótica da canção - Santos, Julio César Ribeiro dos (Universidade Federal de São Carlos, 2023)
The enduring permanence and expressiveness of the sertanejo style of popular song allows spontaneous recognition regarding its ongoing transformation in the most diverse aspects that can be observed, whether in materiality, or in the discursive or social aspects articulated interdependently with it. The general objective of this thesis involves describing, interpreting and proposing an explanation about this transformation, having as specific focuses: (a) the role of language in its dialectical relationship with the social structure in country song texts and the constant transformation of style; and (b) the investigation around the permanence or erasures of the caipira objectified by Darcy Ribeiro (1995) in the so-called sertaneja discursive formations. The theoretical foundation proposes and applies a field of interaction between some elements of Song Semiotics (TATIT [1996] 2012), a theory that pioneers accommodate song texts in the field of linguistic studies, and Critical Discourse Analysis (FAIRCLOUGH, 1989; [1992] 2001, [2005] 2012), which interrelates in an elegant way summarized in an efficient theoretical-methodological model language, discourse and society. I make use of the work of Chitãozinho & Xororó between the years 1970-2022, which, among countless consecrations, actively participated in different ordinances of the field, which implies both the dialogue with countless artists belonging to different genres at different times and the active inclusion in diverse business models. As a corpus, a presentation of a concert linked to the Evidências tour (2017-2020) whose analyzes are more specifically focused on the songs. The show consists of 24 song texts, taken in terms of translation (JAKOBSON, [1959] 2010) of their source texts, these referring to the period 1970-2010. Aiming to increase the concreteness of the analyses, the research includes external observations, semi-structured interviews (CRESWELL, 2010) and personal communications with professionals linked to the pair. Despite the mention of the field and its figurative isotopies enriched by singing in a duet, nasally invested with falsettos and vibratos, which suggests a cohesive link in the style, which is endowed with such material traits in its roots (LIMA, 1972), the results point to the erasure of the caipira described by Ribeiro (1995) in the so-called sertaneja song due to factors that articulate the desire of the artists themselves to disassimilate the social stigmas imputed to them and interests of the Cultural Industry and its constant scope of entertainment in different semantic fillings structured and structuring texts.
In search of evidence: the transformation of sertaneja music in the work of Chitãozinho & Xororó from the perspective of critical discourse analysis and song semiotics
Keywords: Análise crítica do discurso; Semiótica da canção; Canção sertaneja; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA